Analisa Perencanaan Pembangkit Listrik Tenaga Surya Atap dengan Sistem Hybrid di PT. Koloni Timur - Sudarjo, Noor Hajir; Haddin, Muhamad; Suprajitno, Agus (Elektrika, 2022)
This study discusses the Planning of a Rooftop Solar Power Plant with a Hybrid System at PT East Colony Kudus. Themodel is set as a PLTS whose solar panels are adjusted to the roof area of the building. This PLTS is functioned as a newrenewable energy resource (EBT) in the form of a hybrid between PLTS and PLN's electrical energy source, this is done tohelp supply electricity. Parameters determined include: roof area, solar panel capacity, inverter capacity, battery capacityand payback period. The results show that PLTS with a total of 80 solar panels installed with a capacity of each panel 405Watt peak, then obtained a power capacity of 32.4 kilo Watt peak which is divided into 5 arrays, with a solar charger controllerand inverter using a 10kW capacity of 5 units, 80 batteries with a capacity of 400Ah. So that PLTS is able to contribute 39.3%of the total power needed by PT East Colony (electric power from PLN is 60.7%). This hybrid payback period will return after8 years and 7 months.